2022
DOI: 10.1017/jfm.2022.815
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inclination angle on heat transport properties in two-dimensional Rayleigh–Bénard convection with smooth and rough boundaries

Abstract: Using direct numerical simulations, two-dimensional tilted Rayleigh–Bénard convection (RBC) is studied in both smooth and roughness-facilitated convection cells of double aspect ratio ( $\varGamma =2$ ) for air as a working fluid. We investigate the effect of inclination angle ( $0^{\circ } \leq \phi \leq 90^{\circ }$ ) on heat flux ( $Nu$ ), Reynolds number ( $Re$ ) and flow structures. In a Rayleigh number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…An alternate approach is to apply a temperature difference across the water‐saturated side walls as well as between the top and bottom of the convection chamber, thereby allowing the side walls to augment rather than deplete the supersaturation field. Thermal convection driven by side walls is typically referred to as vertical convection or tilted Rayleigh‐Bénard convection, and has been studied in the literature (Chand et al., 2022; Shishkina, 2016; Q. Wang et al., 2021). We will build on that work by exploring how various specifications of side wall temperature and moisture can enhance the supersaturation, the LWC, and as a consequence the droplet collision rate.…”
Section: Introductionmentioning
confidence: 99%
“…An alternate approach is to apply a temperature difference across the water‐saturated side walls as well as between the top and bottom of the convection chamber, thereby allowing the side walls to augment rather than deplete the supersaturation field. Thermal convection driven by side walls is typically referred to as vertical convection or tilted Rayleigh‐Bénard convection, and has been studied in the literature (Chand et al., 2022; Shishkina, 2016; Q. Wang et al., 2021). We will build on that work by exploring how various specifications of side wall temperature and moisture can enhance the supersaturation, the LWC, and as a consequence the droplet collision rate.…”
Section: Introductionmentioning
confidence: 99%
“…Variations of these problems include the effect of tilting the rough walls, for triangular (Chand, Sharma & De 2022) and ratchet-shaped (Jiang et al 2023) surfaces, and the heat transfer enhancement that can be obtained by moving the rough plates (Jin et al 2022). Zhang et al (2018) showed computationally that in some cases with small roughness heights, roughness can actually decrease the rate of heat transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Mansour et al [22] experimentally investigated nanoliquids in an inclined tube and demonstrated the influence of inclination angles on the convective heat transfer process. Chand et al [23] conducted direct numerical simulations on inclined RBC and observed smooth and roughness-facilitated convection cells of double aspect ratio (Γ = 2) for air as a working fluid. Liang and Acrivos [24] were the first to study the linear stability of natural convection in inclined geometry, wherein a Rayleigh number expression for steady longitudinal rolls (LRs) was derived using the perturbation method.…”
Section: Introductionmentioning
confidence: 99%